A biomimetic multi-layered collagen-based scaffold for osteochondral repair - O'BRIEN, FERGAL (My University, 2014)
Cartilage and osteochondral defects pose a significant challenge in orthopedics. Tissue engineering has shown promise as a potential method for the treatment of such defects; however, a long-lasting repair strategy has yet to be realized. This study focuses on the development of a layered construct for osteo- chondral repair, fabricated through a novel ``iterative layering?? freeze-drying technique. The process involved repeated steps of layer addition followed by freeze-drying, enabling control over material composition, pore size and substrate stiffness in each region of the construct, while also achieving a seamlessly integrated layer structure. The novel construct developed mimics the inherent gradient struc- ture of healthy osteochondral tissue: a bone layer composed of type I collagen and hydroxyapatite (HA), an intermediate layer composed of type I collagen, type II collagen and HA and a cartilaginous region composed of type I collagen, type II collagen and hyaluronic acid. The material properties were designed to provide the biological cues required to encourage infiltration of host cells from the bone marrow while the biomechanical properties were designed to provide an environment optimized to promote differen- tiation of these cells towards the required lineage in each region. This novel osteochondral graft was shown to have a seamlessly integrated layer structure, high levels of porosity (>97%), a homogeneous pore structure and a high degree of pore interconnectivity. Moreover, homogeneous cellular distribution throughout the entire construct was evident following in vitro culture, demonstrating the potential of this multi-layered scaffold as an advanced strategy for osteochondral defect repair.
PUBLISHED
Keywords: Collagen; Osteochondral defects